2012
DOI: 10.1007/s10549-011-1943-y
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life, psychological distress, and adverse events in postmenopausal women with breast cancer who receive tamoxifen, exemestane, or anastrozole as adjuvant endocrine therapy: National Surgical Adjuvant Study of Breast Cancer 04 (N-SAS BC 04)

Abstract: Health-related quality of life (HRQOL), symptoms of depression, and adverse events (AEs) were compared between Japanese postmenopausal patients with hormone-sensitive breast cancer (BC) who received adjuvant tamoxifen, exemestane, or anastrozole in an open-labeled, randomized, multicenter trial designated as the National Surgical Adjuvant Study of Breast Cancer (N-SAS BC) 04 substudy of the Tamoxifen Exemestane Adjuvant Multinational (TEAM) trial. During the first year of treatment, HRQOL and symptoms of depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
27
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 40 publications
4
27
0
1
Order By: Relevance
“…Differently, ES scores were similar in the three arms. As for depression issues, CES-D scores were largely comparable in the three groups [34,36].…”
Section: Switch Schedule Tamoxifen-aromatase Inhibitormentioning
confidence: 92%
“…Differently, ES scores were similar in the three arms. As for depression issues, CES-D scores were largely comparable in the three groups [34,36].…”
Section: Switch Schedule Tamoxifen-aromatase Inhibitormentioning
confidence: 92%
“…On the other hand, HRQOL scores were similar between Caucasian patients treated with adjuvant tamoxifen and adjuvant AIs [16,17]. A better HRQOL observed in Japanese patients taking tamoxifen may be due to the fact that a fatigue was significantly less frequent in Japanese patients taking tamoxifen than Caucasian patients [15]. One of the reasons for this might be due to the different metabolism of tamoxifen between Japanese patients and Caucasian patients.…”
mentioning
confidence: 86%
“…For instance, a variant allele of CYP2D6*10 having a decreased activity is found in 51% of Asians; however, it is rare in Caucasians [13]. All these results suggest that the efficacy of tamoxifen may differ between races.Health-related Quality of Life (HRQOL) scores were higher in Japanese women with breast cancer who took adjuvant tamoxifen compared with adjuvant anastrozole or exemestane [15]. On the other hand, HRQOL scores were similar between Caucasian patients treated with adjuvant tamoxifen and adjuvant AIs [16,17].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some data suggest that there is a correlation between the reduction of estrogen and the onset of depression (Bower, 2008;Halbreich, 1997;Massie, 2004); therefore, it is possible that AI therapy may increase the risk of depression among cancer survivors. Several studies conducted among Japanese breast cancer survivors showed no difference in depressive symptoms, as measured using the Center for Epidemiological Studies-Depression (CES-D) scale, among women treated with exemestane, tamoxifen, or anastrozole during the first year of treatment, and no difference in depressive symptoms among breast cancer survivors who switched from tamoxifen to anastrozole compared to those who remained on tamoxifen (Ohsumi et al, 2011;Takei, 2012). In general, these studies are limited by the fact that they have been conducted within clinical trials, where patients are healthier than the general breast cancer population, and the comparison group is on other hormonal therapies, which may be associated with psychosocial side effects themselves.…”
Section: Introductionmentioning
confidence: 99%